SCHOOL PRINCIPALS' RESPONSES AND CHALLENGES IN THE IMPLEMENTATION OF PERMENDIKBUDRISTEK NUMBER 40 OF 2021 - Ikka Kartika; Muhammad Firman; Margono Margono; Abdul Rohman (Lembaga Pengembangan Pembelajaran Penelitian dan Pengabdian Masyarakat Universitas PGRI Mahadewa Indonesia, 2023)
This study aims to explore principals' responses and understandings related to the implementation of Permendikbudristek Number 40 of 2021 Â on the assignment of teachers as principals, as well as identify the challenges faced in implementing the policy. The research used qualitative methods involving observation, interviews, and documentation. The results show that the implementation of the policy has been carried out in stages and coordinated. However, in responding to the policy, there are several challenges faced. One of them is the lack of qualified teachers to become principals, which has an impact on the selection and assignment process. Thus, the implementation of Permendikbudristek Number 40 of 2021 has the potential to improve the quality of education in primary schools in Sukabumi district. To overcome the challenges, it is recommended that the government evaluate the burdensome articles. Good coordination between all relevant parties is needed to reach a mutual agreement. This research contributes to the understanding of principals' responses to the implementation of the policy on teacher assignment as principals and identifies the challenges faced. The results of this study can be the basis for developing more effective policies and strategies in improving the quality of principal leadership and education in primary schools.